ANALISIS PENGARUH WORK ENGAGEMENT SEBAGAI MEDIATOR ANTARA KEPEMIMPINAN TRANSFORMASIONAL DAN CHALLENGE STRESSORS DENGAN TURNOVER INTENTION PADA KARYAWAN TETAP DI LEMBAGA PENDIDIKAN INDONESIA AMERIKA - Tony Hartono; Yangki Hartijasti (JURNAL STUDI MANAJEMEN ORGANISASI, 2017)
The study aims to examine the effect of work engagement as a mediator on transformational leadership and challenge stressors with turnover intention. The study was conducted on 79 permanent employees working in all branch offices in one of the non formal education institutions spread in Jakarta, West Java, Central Java and East Java. The results showed that work engagement has influence as a mediator between transformational leadership and challenge stressors to turnover intention. The results also show that work engagement has the most significant role to increase the influence of transformational leadership on turnover intention because it has the greatest total effect value.